2003
DOI: 10.1083/jcb.200304035
|View full text |Cite
|
Sign up to set email alerts
|

Morphologically distinct microtubule ends in the mitotic centrosome of Caenorhabditis elegans

Abstract: During mitosis, the connections of microtubules (MTs) to centrosomes and kinetochores are dynamic. From in vitro studies, it is known that the dynamic behavior of MTs is related to the structure of their ends, but we know little about the structure of MT ends in spindles. Here, we use high-voltage electron tomography to study the centrosome- and kinetochore-associated ends of spindle MTs in embryonic cells of the nematode, Caenorhabditis elegans. Centrosome-associated MT ends are either closed or open. Closed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
133
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(153 citation statements)
references
References 38 publications
18
133
1
Order By: Relevance
“…This experimental approach led to the identification of three different types of microtubule plus-end morphologies: (1) extended ends, which are typical of growing microtubules; (2) ram's-horn-like ends, which are characteristic of disassembling microtubules; and (3) blunt ends, which reflect a metastable state. More recently, a fourth microtubule plus-end morphology, flared, has been identified in electrontomographic studies of the mitotic kinetochores of Caenorhabditis elegans (O'Toole et al, 2003). To date, no systematic studies of microtubule plus-end geometries have been reported in plants.…”
mentioning
confidence: 98%
“…This experimental approach led to the identification of three different types of microtubule plus-end morphologies: (1) extended ends, which are typical of growing microtubules; (2) ram's-horn-like ends, which are characteristic of disassembling microtubules; and (3) blunt ends, which reflect a metastable state. More recently, a fourth microtubule plus-end morphology, flared, has been identified in electrontomographic studies of the mitotic kinetochores of Caenorhabditis elegans (O'Toole et al, 2003). To date, no systematic studies of microtubule plus-end geometries have been reported in plants.…”
mentioning
confidence: 98%
“…We next determined MT polarity by identifying capped MT ends, which represent minus ends that are protected by the -TURC (O'Toole et al, 1999;O'Toole et al, 2003). The other end of these MTs are almost certainly growing plus ends, given the MBC wash-out.…”
Section: Growing Microtubule Ends Are Mostly Flaredmentioning
confidence: 99%
“…However, sheet-like MT plus ends are rare in yeasts and human cells. Here, a majority of MT ends are flared, meaning that most or all of their tubulin protofilaments splay out from the MT axis (O'Toole et al, 1999;O'Toole et al, 2003;McIntosh et al, 2008). In an effort to understand the diversity seen in these reports, we have studied growing MT ends in Schizosaccharomyces pombe after release from a MT-depolymerising drug, using electron tomography to answer the question how MTs grow inside a cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been demonstrated that, like depolymerizing microtubules in vitro, kinetochore microtubule plus-ends in yeast, worms, Drosophila and vertebrate somatic cells have bent protofilaments [142][143][144][145][146]. Definitive work by Grishchuk and McIntosh showed that deletion of all the three minus-end directed motors found in the fission yeast genome did not abolish the poleward movement of chromosomes during anaphase [94].…”
Section: Force Generation By Microtubule Depolymerization From Plus-endsmentioning
confidence: 99%